Yoga untuk Mengurangi Nyeri Disminorhea pada Remaja Perempuan Usia Sekolah - Feni Dwiyanti; Ni Kadek Cahyaningsih; Suci Rohandayani; Cahyaningrum; Hapsari Windayanti; Heni Setyowati (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2022)
Dysmenorrhea is pain during menstruation caused by uterine muscle spasms. The cause of dysmenorrhea is due to increased levels of prostaglandins. This increase will result in uterine contractions and vasoconstriction of blood vessels. Blood flow to the uterus decreases so that the uterus does not get an adequate oxygen supply which causes pain. The intensity of pain is influenced by the individual's description of pain or the perception of the experience of pain. Treatment efforts to reduce dysmenorrhea are pharmacological therapy such as analgesic drugs, hormonal therapy therapy with non- steroidal anti-prostaglandin drugs and cervical canal dilatation. Based on the results of the analysis by observing problems that occur in society where adolescents in Thekelan hamlet still lack knowledge about reproductive health, independent management of dysminorrhea pain, the number of deviant behaviors among adolescents, for example smoking, unhealthy lifestyles. So we need to do community service about yoga to reduce dysminore pain, it is hoped that adolescents can increase knowledge about reproductive health, self-management at home during dysminorrhea pain, and improve daily habit patterns that deviate into positive activities. Yoga is a technique that teaches techniques such as relaxation, breathing, and body position to increase strength, balance and reduce pain. The purpose of community servise carried out in thekelan village with a number of respondents 22 school age girl is to increase knowledge and insight to adolescents so that they can overcome dysmenorrehea pain non-pharmacologically by yoga exercise. Community service is carried out in 5 stages. The first stage is to find respondens, the second stage is counseling, the third stage is mentoring, the fourtd stage is implementation, the fifth stage is evaluation by filling out post-test questionnaires. The result obtained are teenagers can understand the benefit of yoga to reduce disminorrhea pain. There is an increase in knowledge in adolescents seen from the result of the pre-test and post-test questinnaires. As many as 18,2% adolescents with good knowledge, 81,8% adolescents with poor knowledge. There is increase of 77,2% before and after community service.Community service aktivites about yoga to reduse dysmenorrhea pain in school-age adolescent grils in thekelan village have been carried out well. The service activites carried out received good and enthusiastic responses from respondent. There in the knowledge of adolescent grils about yoga to reduce dysmenorrhea pain which in known from the increase in the average pre-test and post-test csores. AbstrakDismenore (Disminorhea) adalah nyeri selama menstruasi yang disebabkan oleh kejang otot uterus. Penyebab terjadinya dismenore dikarenakan adanya peningkatan kadar prostaglandin. Peningkatan ini akan mengakibatkan kontraksi uterus dan vasokonstriksi pembuluh darah. Aliran darah yang menuju terus menurun sehingga uterus tidak mendapat suplai oksingen yang adekuat yang menyebabkan nyeri intensitas nyeri dipengaruhi oleh deskripsi individu tentang nyeri atau persepsi pengalaman nyeri. Upaya penanganan untuk mengurangi dismenore adalah dengan pemberian terapi farmakologi seperti obat analgetik, terapi hormonal terapi dengan obat non steroid anti prostaglandin dan dilatasi kanalis servikanalis. Berdasarkan hasil analisa dengan mengobservasi masalah yang terjadi dimasyarakat dimana remaja di dusun Thekelan masih kurang pengetahuan tentang kesehatan reproduksi, penanganan mandiri nyeri disminore, banyaknya perilaku yang menyimpang dikalangan remaja misalnya merokok, pola hidup yang kurang sehat. Sehingga kami perlu melakukan pengabdian kepada masyarakat tentang yoga untuk mengurangi nyeri disminore diharapkan remaja dapat meningkatkan pengetahuan tentang kesehatan reprosukdi, penangangan mandiri di rumah saat nyeri disminore, dan memperbaiki pola kebiasaan sehari-hari yang menyimpang menjadi kegaitan-kegiatan yang positif. Yoga merupakan tehnik yang mengajarkan seperti tehnik relaksasi, pernafasan, dan posisi tubuh untuk meningkatkan kekuatan, keseimbangan dan mengurangi rasa nyeri. Tujuan dilakukan pengabdian masyarakat yang dilakuakn di Desa Thekelan dengan jumlah responden 22 remaja perempuan usia sekolah adalah untuk menginkatkan pengetahuan serta wawasan kepada remaja untuk dapat mengatasi nyeri disminore secara non-farmakologi yaitu dengan cara senam yoga. Pengabdian kepada masyarakat ini dilakukan dengan 5 langkah yakni Langkah Pertama tahap mencari rensponde, Tahap kedua penyuluhan tentang pelatihan yoga, Tahap ketiga pendampingan pelatihan yoga, Tahap ke empat pelaksaan yoga, Tahap kelima evaluasi dengan pengisian kuesoner post-test.Hasil yang diperoleh adalah remaja memahami manfaat yoga untuk mengurangi nyeri disminore. Terjadi peningkatan pengetahuan pada remaja dilihat dari hasil kuesoner pre-test dan post-test. Sebanyak 18,2 % remaja yang pengetahuannya baik, 81,8 % remaja masih kurang. Terdapat peningkatan yaitu 77,2 % sebelum dan sesudah dilakukannya pengabdian kepada masyarakat. Kegiatan Pengabdian kepada masyarakat tentang Yoga untuk mengurangi nyeri disminore pada remaja perempuan usia sekolah di desa Thekelan, Batur telah terlaksana dengan baik. Kegiatan Pengabdian yang dilakukan mendapatkan respon baik dan antusias dari responden. Adanya peningkatan pengetahuan dari remaja perempuan tentang yoga untuk mengurangi nyeri disminore yang diketahui dari meningkatnya skor rata-rata pre test dan post test di Desa Thekelan, Batur.